Marine Compounds and Cancer 2020 - Honecker, Friedemann; Dyshlovoy, Sergey A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The very first marine-derived anticancer drug, Cytarabine (aka Ara-C, Cytosar-U®), was approved by the FDA in 1969 for the treatment of leukemia. At the beginning of 2021, the list of approved marine-derived anticancer drugs consists of nine substances, five of which received approval within the last two years, demonstrating the rapid evolution of the field. The current book is a collection of scientific articles related to the exponentially growing field of anticancer marine compounds. These articles cover the whole field, from agents with cancer-preventive activity, to novel and previously characterized compounds with anticancer activity, both in vitro and in vivo, as well as the latest status of compounds under clinical development.